Complex Reconfiguration of DNA Nanostructures1. Issue 29 (4th June 2014) - Wei, Bryan; Ong, Luvena L.; Chen, Jeffrey; Jaffe, Alexander S.; Yin, Peng
Abstract Nucleic acids have been used to create diverse synthetic structural and dynamic systems. Toehold‐mediated strand displacement has enabled the construction of sophisticated circuits, motors, and molecular computers. Yet it remains challenging to demonstrate complex structural reconfiguration in which a structure changes from a starting shape to another arbitrarily prescribed shape. To address this challenge, we have developed a general structural‐reconfiguration method that utilizes the modularly interconnected architecture of single‐stranded DNA tile and brick structures. The removal of one component strand reveals a newly exposed toehold on a neighboring strand, thus enabling us to remove regions of connected component strands without the need to modify the strands with predesigned external toeholds. By using this method, we reconfigured a two‐dimensional rectangular DNA canvas into diverse prescribed shapes. We also used this method to reconfigure a three‐dimensional DNA cuboid.